Volume 12: Mechanics of Solids, Structures and Fluids 2008
DOI: 10.1115/imece2008-67390
|View full text |Cite
|
Sign up to set email alerts
|

Towards Toughening and Understanding of Silica Aerogels: MD Simulations

Abstract: This presentation focuses on Molecular-Dynamics simulations of silica. It is aimed at shedding light on the stiffness, strength, and toughness of silica, chemically modified silica and ultimately of the silica-based aerogel. Various aspects of the simulation process will be discussed, such as the methods used for creating amorphous silica, applying strain, maintaining an isothermal condition, and so on. Results will be presented for amorphous silica. This is preliminary work leading towards the first author’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The strain rate is larger than the one used in laboratory tests; however it has been shown that smaller values of strain rate do not change the results significatively [33]. At higher strain rates, the speed of the atoms, and consequently the temperature of the sample, tend to increase.…”
Section: Mechanical Characterization Of the Samplesmentioning
confidence: 86%
See 1 more Smart Citation
“…The strain rate is larger than the one used in laboratory tests; however it has been shown that smaller values of strain rate do not change the results significatively [33]. At higher strain rates, the speed of the atoms, and consequently the temperature of the sample, tend to increase.…”
Section: Mechanical Characterization Of the Samplesmentioning
confidence: 86%
“…Previous studies on modeling bulk silica where used to select the combination of strain rate and the damping to use in the Langevin dynamics without affecting the results of the simulation [33].…”
Section: Mechanical Characterization Of the Samplesmentioning
confidence: 99%